Functionally Significant Features in the 5' Untranslated Region of the ABCA1 Gene and Their Comparison in Vertebrates - Dvořák, Pavel; Leupen, Sarah; Souček, Pavel (Cells, 2019)
Single nucleotide polymorphisms located in 5' untranslated regions (5'UTRs) can regulate gene expression and have clinical impact. Recognition of functionally significant sequences within 5'UTRs is crucial in next-generation sequencing applications. Furthermore, information about the behavior of 5'UTRs during gene evolution is scarce. Using the example of the ATP-binding cassette transporter A1 (<ovid:i>ABCA1</ovid:i>) gene (Tangier disease), we describe our algorithm for functionally significant sequence finding. 5'UTR features (upstream start and stop codons, open reading frames (ORFs), GC content, motifs, and secondary structures) were studied using freely available bioinformatics tools in 55 vertebrate orthologous genes obtained from Ensembl and UCSC. The most conserved sequences were suggested as hot spots. Exon and intron enhancers and silencers (sc35, ighg2 cgamma2, ctnt, gh-1, and fibronectin eda exon), transcription factors (TFIIA, TATA, NFAT1, NFAT4, and HOXA13), some of them cancer related, and microRNA (hsa-miR-4474-3p) were localized to these regions. An upstream ORF, overlapping with the main ORF in primates and possibly coding for a small bioactive peptide, was also detected. Moreover, we showed several features of 5'UTRs, such as GC content variation, hairpin structure conservation or 5'UTR segmentation, which are interesting from a phylogenetic point of view and can stimulate further evolutionary oriented research.
Keywords: Phylogeny; introny; nukleotidové motivy; Humans; zvířata; Open Reading Frames; RNA Splicing; otevřené čtecí rámce; Introns; messenger RNA; ABCA1 protein; 5' nepřekládaná oblast; konzervovaná sekvence; Base Sequence; savci; sekvence nukleotidů; anotace sekvence; Molecular Sequence Annotation; Enhancer Elements, Genetic; sekvence aminokyselin; Base Composition; Nucleic Acid Conformation; ATP Binding Cassette Transporter 1; Vertebrates; Nucleotide Motifs; Animals; Amino Acid Sequence; lidé; RNA, Messenger; 5' Untranslated Regions; zastoupení bazí; sestřih RNA; fylogeneze; Mammals; konformace nukleové kyseliny; Conserved Sequence; zesilovače transkripce